Analisis Efisiensi Biaya Full Costing Dan Activity Based Costing Method Di Da Vienna Boutique Hotel - Candra, Deki; Husda , Anggun Permata (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This research aims to analyze the comparison of the application of cost methods between full costing and activity based costing, then test which method has a better level of cost efficiency between the two methods. The cost method is used to calculate the costs used by an entity to produce products or services through precise measurements. Management as a cost control function must be able to optimize profits, by keeping costs as low as possible so as to create a greater positive difference in income. This research is qualitative research with descriptive comparative design as an analysis technique. The data used for this research is primary data. Based on research conducted, calculations using activity based costing have a better level of efficiency than the full costing method, amounting to IDR 17,863,276. A better level of efficiency is due to calculations using activity based costing where basic room prices can be accurately charged based on the actual cost of resource usage.